Assessment and management of women with heavy menstrual bleeding in Kenya: a best practice implementation project. Issue 2 (18th June 2021) - Akumu, Lydia A.; Ratemo, Stanley N.; Owende, Philomena
ABSTRACT: Aim: The aim of this evidence implementation project is to make a contribution to promoting evidence-based practice in the assessment and management of women with heavy menstrual bleeding (HMB) attending the gynaecology outpatient clinic at Kenyatta National Hospital (KNH) and thereby improve patient outcomes and resource utilization. Methods: The evidence implementation project was carried out at the gynaecology outpatient clinic of the largest referral facility in Kenya. The Joanna Briggs Institute Practical Application of Clinical Evidence System and Getting Research into Practice audit and feedback tool were used. A baseline audit was conducted using a sample of 40 patient files; this was followed by interventions such as trainings, developing of visual tools and updating of protocols. A follow-up audit was then conducted 4 months post intervention. Results: Baseline audit results demonstrated varying results in each of the nine criteria selected. Four of the criteria recorded less than 51% compliance, with two of these recording 0% compliance. Postintervention results showed a remarkable increase in most of the audit criteria selected, with eight of these having compliance levels of 90% or more. Conclusion: The implementation project served the dual purpose of enlightening health care workers on best practices and educating patients on what they need to know about their condition. This led to an overall improvement in the management of HMB.